Analisis unsur intrinsik dan nilai krakter cerita pendek dalam buku "saya senang berbahasa indonesia" kelas V sekolah dasar - Ida Mawarni; Jenny Indrastoeti Siti Poerwanti; Matsuri Matsuri (Didaktika Dwija Indria, 2022)
The study was intended to identify intrinsic elements and character education value in the collection of short stories found in the Indonesian textbook at the primary school, entitled Saya Senang Berbahasa Indonesia SD Jilid 5. To find out, the study therefore employs qualitative descriptive methods. The results of this study indicate that the book's collection of short stories had character education. A short story of Hadiah Istimewa has character value that values achievement, friendliness, and religion. A short story Mabuk karena Ngantuk has an inquisitive, environmental, and social value. Ani yang Pelupa short story has a character value: responsibility, preoccupation with reading, curiosity, friendships, social concern, hard work, and achievement. Abu Nawas Tidak Bisa Kehujanan short story has the value of character discipline, tolerance, religion, responsibility, respect his achievements, curiosity, creative, and hard work. Menebus Kesalahan short story has the character value of hard work, responsibility, and love of peace.